2008
DOI: 10.2752/089279308x274047
|View full text |Cite
|
Sign up to set email alerts
|

Justifying Attitudes toward Animal Use: A Qualitative Study of People's Views and Beliefs

Abstract: Animal use" is a contentious topic that refers to practices involving the utilization of non-human animals by human beings. These practices often evoke strong and emotional reactions from opposing parties, and individuals can hold incongruent views concerning different ways in which animals are used. Yet previous research in this area has tended to portray attitudes toward animal use as uni-dimensional (rather than distinguishing between different types of use), and the field has been dominated by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 34 publications
9
85
0
3
Order By: Relevance
“…Fatores como o sexo (Paul, 2000), a vivência com animais de estimação (Ellingsen et al, 2010;Furnham, McManus, & Scott, 2003;Paul, 2000;Paul & Serpell, 1993), a personalidade (Mathews & Herzog, 1997), a utilidade do animal (Knight & Barnett, 2008;Wells & Hepper, 1997), bem como a crença nas capacidades mentais dos animais (Apostol, Rebega, & Miclea 2013;Hills, 1995) têm sido assinalados como tendo uma importante influência na empatia, sobretudo quando relacionados com as atitudes para com os animais.…”
Section: Discussionunclassified
“…Fatores como o sexo (Paul, 2000), a vivência com animais de estimação (Ellingsen et al, 2010;Furnham, McManus, & Scott, 2003;Paul, 2000;Paul & Serpell, 1993), a personalidade (Mathews & Herzog, 1997), a utilidade do animal (Knight & Barnett, 2008;Wells & Hepper, 1997), bem como a crença nas capacidades mentais dos animais (Apostol, Rebega, & Miclea 2013;Hills, 1995) têm sido assinalados como tendo uma importante influência na empatia, sobretudo quando relacionados com as atitudes para com os animais.…”
Section: Discussionunclassified
“…First, comments were compared to Likert responses and classified as: support regardless of other factors (SR), conditional support (CS), no support (NS), and uncertain or indifference (UN). Comments were grouped into themes extracted from respondents' answers following the methods described by Knight and Barnett (2008). All themes were evaluated according to the emphasis given by the respondents, and one comment can have more than one identified theme.…”
Section: Analysis Of Qualitative Datamentioning
confidence: 99%
“…Interestingly, participants did not raise concerns around the need for alternative approaches in the BS when the use of non-GM animals was proposed. Knight and Barnett (2008) identified that support of some participants for the use of animals in medical research was based upon the belief that there were no suitable alternatives to using animals. Greek et al (2010) concluded that people are more likely to support the use of animals if the research is likely to aid in the treatment and decrease the suffering of human patients, but that people are less likely to support animal use in basic research.…”
Section: Alternatives and New Paradigmsmentioning
confidence: 99%
“…It is moral because it tells us something about the right or the wrong way to treat animals, whose welfare and flourishing can be promoted or harmed by our actions. The word attitude to animals is already used in studies to describe people's views on animals and their treatment (Knight and Barnett 2008;Matthews and Herzog 1997;Serpell 2004) and therefore it makes sense to use a term that is already in use. We defined fundamental moral attitude as the fundamental convictions of a person, or a group of people, on the hierarchical position of animals, their value, doing good (to care for and protect), and their rights.…”
Section: Methodsmentioning
confidence: 99%
“…Knight et al 2003, andBarnett 2008) found that the degree of mental abilities of animals were one determinant in people's attitude to animals. The more mentally developed and sentient an animal species is the least acceptable is its use for human purposes.…”
Section: The Theoretical Framework Of the Modelmentioning
confidence: 99%